2008
DOI: 10.1088/0004-637x/690/1/330
|View full text |Cite
|
Sign up to set email alerts
|

CHANDRAX-RAY SPECTROSCOPY OF THE FOCUSED WIND IN THE CYGNUS X-1 SYSTEM. I. THE NONDIP SPECTRUM IN THE LOW/HARD STATE

Abstract: We present analyses of a 50 ks observation of the supergiant X-ray binary system Cygnus X-1 (Cyg X-1)/ HDE226868 taken with the Chandra High Energy Transmission Grating Spectrometer (HETGS). Cyg X-1 was in its spectrally hard state and the observation was performed during superior conjunction of the black hole, allowing for the spectroscopic analysis of the accreted stellar wind along the line of sight. A significant part of the observation covers X-ray dips as commonly observed for Cyg X-1 at this orbital pha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
116
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 95 publications
(136 citation statements)
references
References 79 publications
20
116
0
Order By: Relevance
“…For example, Feng & Cui (2002) discuss a long dip of at least ∼3 ks that shows complex substructure. Prolonged periods of increased absorption are also clearly seen in the long uninterrupted observations possible with Chandra (Hanke et al 2008). Given these previous measurements and the size of our sample, the detection of several strong absorption events as discussed in Sect.…”
Section: Discussion and Comparison To Earlier Resultssupporting
confidence: 64%
See 2 more Smart Citations
“…For example, Feng & Cui (2002) discuss a long dip of at least ∼3 ks that shows complex substructure. Prolonged periods of increased absorption are also clearly seen in the long uninterrupted observations possible with Chandra (Hanke et al 2008). Given these previous measurements and the size of our sample, the detection of several strong absorption events as discussed in Sect.…”
Section: Discussion and Comparison To Earlier Resultssupporting
confidence: 64%
“…Boroson & Vrtilek (2010) classified 102 of these observations as hard states and used them to demonstrate the orbital variability of absorption in the hard state, but did not have enough data taken during softer states. At the same time, higher sensitivity snapshots at different φ orb with Chandra (Miller et al 2005;Hanke et al 2009;Miškovičová et al 2015) and Suzaku Miller et al 2012;Yamada et al 2013) revealed a complex structure of the wind with highly Grinberg et al (2013).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Some disagreement between the MEG and HEG spectrum in the 3-5 keV energy range is an indication of pileup (discussed in more detail in Section 2.2), because light is dispersed over smaller angles with the MEG as compared to the HEG. To test for possible non-linear effects in the HEG arms, we applied the pileup correction simple gpile2 (Nowak et al 2008;Hanke et al 2009) with the physical spectral models described below. We found that the MEG and HEG arms could be fit simultaneously with less than 1% of HEG counts being affected by pileup.…”
Section: Fit To the Hetg Spectrummentioning
confidence: 99%
“…Because of its brightness and persistent emission, Cyg X-1 is one of the best studied BHs. In addition to studies of snapshot observations (e.g., Gierliński et al 1999;Di Salvo et al 2001;Frontera et al 2001;Makishima et al 2008;Hanke et al 2009), most recent work has concentrated on the long-term behavior of the source from a monitoring campaign with the Rossi X-Ray Timing Explorer (RXTE) at a two week sampling that started in 1998 and is still ongoing (Pottschmidt et al 2003;Gleissner et al 2004a,b;Axelsson et al 2005;Wilms et al 2006, and references therein). The motivation of the present work was to fill the gap between the biweekly time scale and individual RXTE pointings with an intensive quasi-continuous observation spanning 10 days.…”
Section: Introductionmentioning
confidence: 99%